Association of Pro-social Behavior with Agentic and Communal Narcissism among Young Adults - Shah, Inayat; Zia, Kianat; Alam, Aftab (The Lighthouse Journal of Social Sciences, 2023)
Narcissism is widely regarded as unfavorable in terms of its potential to benefit others. The objective of this study was to examine the role of narcissism in promoting prosocial behavior. This study aims to explore the association between agentic and communal narcissism among individuals, as well as their link with prosocial conduct among young individuals. This study employed a cross-sectional technique and a correlational design to investigate the relationship between communal narcissism, prosocial tendencies, and narcissistic personality traits. Data was obtained from a sample of 250 participants using the Communal Narcissistic Inventory (CNI), Prosocial Tendencies Measure (PTM), and Narcissistic Personality Inventory (NPI). The results of the study shed light on the fact that both grandiose and non-pathological narcissism are positively linked to pro-social behaviors. Additionally, there are connections between communal narcissism and non-pathological narcissism with self-reported altruistic pro-social activities.